Factors Determining the Financial Condition on the Example of WSE Listed Companies - Bolek, Monika; Gniadkowska-Szymańska, Agata (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The goal of this paper is related to the assessment of companies’ condition on a capital market that is an important information for stakeholders, including investors and managers. The article presents assessment methods related to value creation, solvency and growth potential. Methodology: The measure of the company’s financial situation based on Altman’s Z-Score, Tobin’s Q and EPS growth factor is proposed in this study as a variable that can be influenced by strategies reflected in the levels of financial ratios. The paper provides a new approach to the way the financial condition can be appraised. Results of the research: Basing on data analysis it was found that the companies’ situation related to the 3-year EPS growth, bankruptcy probability and growth potential is determined by total assets in a negative way and return on assets in a positive way. The condition of the companies related to the 5-year EPS growth, bankruptcy probability and growth potential is determined by the capital structure and return on equity in a positive way. Short term growth is therefore determined by assets management and long term growth by the optimization of capital structure. In addition it was found that there are differences between companies in a good and weak condition in terms of the strategies they implement.